Implementasi dan Problematika Gerakan Literasi di SD Negeri 2 Palangka - Diana Putri Wahyu Romadhona; Norliana Norliana; Resnawati Resnawati; Misnawati Misnawati; Alifiah Nurachmana; Nirena Ade Christy; Yulina Mingvianita (Journal of Student Research, 2023)
The purpose of this paper is to (1) describe the concepts of literacy in elementary schools, (2) describe the implementation of literacy activities in elementary schools, (3) describe the problems of literacy movement in the field in elementary schools. The approach used in this study is a qualitative approach. The method used in this research is literature review and observation. The results showed that literacy activities at SD Negeri 2 Palangka were implemented in three stages, namely the habituation stage, the development stage and the learning stage. However, the implementation of the literacy movement program in schools, especially in SD Negeri 2 Palangka, is not free from various problems. Based on observations, these problems come from 2 factors, that is called internal factors and external factors. The internal factors that cause problems in the literacy movement in SD Negeri 2 Palangka include the readiness of students, infrastructure and availability of funds. Meanwhile, the external factors that cause problems in literacy movement activities in SD Negeri 2 Palangka include community support and government support.